Why Tech Companies Don't See Their Biggest Problems Coming - Mitroff, Ian (MIT Sloan Management Review, 2018)
Technology companies, such as Facebook, often fail to make crisis management a central feature of their operations, thanks to five blind spots to which they're especially susceptible. Recognizing these shortcomings is the first imperative; the next is developing a well-designed crisis-management program that includes several key features. All tech companies should take heed, because failing to reflect - and then act - can worsen the consequences of crises that come down the pike.